Establishing Cycles for Nationally Determined Mitigation Contributions or Commitments - Moarif, Sara (OECD Publishing, 2015)
Parties to the UN Framework Convention on Climate Change (UNFCCC) are currently negotiating a climate change agreement scheduled for adoption at the 21st Conference of the Parties in December 2015. At the centre of the new agreement are nationally determined contributions (NDCs). These are the objectives and actions relating to mitigation or other aspects of climate change responses that countries are willing to put forward internationally and be bound by in some way. This paper seeks to clarify and discuss ideas contained in the draft agreement and draft decision text for the 2015 agreement that may serve to enhance the dynamism and ambition of nationally determined mitigation contributions or commitments (NDMCs). Provisions for ambition and dynamism are included in the procedures framing NDMCs, namely common, regular communications and the requirement that NDMCs become more ambitious over time. Several multilateral processes are also proposed, which might influence the ambition of NDMCs in terms of their content and implementation. The paper discusses proposals for a clarification exercise, a regular global stocktake, and individual assessment and review processes contained with the transparency system and a potential facilitative compliance and implementation system. There are implementation challenges associated with all proposals, though overall these could encourage countries to maximise effort, and provide an opportunity for countries to revise and update their contributions and commitments at regular intervals
Keywords: Energy; Environment